A 19-kDa C-terminal tryptic fragment of the alpha chain of Na/K-ATPase is essential for occlusion and transport of cations. - Karlish, S J (1990)
Tryptic digestion of pig renal Na/K-ATPase in the presence of Rb and absence of Ca ions removes about half of the protein but leaves a stable 19-kDa membrane-embedded fragment derived from the alpha chain, a largely intact beta chain, and essentially normal Rb- and Na-occlusion capacity. Subsequent digestion with trypsin in the presence of Ca or absence of Rb ions leads to rapid loss of the 19-kDa fragment and a parallel loss of Rb occlusion, demonstrating that the fragment is essential for occlusion. The N-terminal sequence of the 19-kDa fragment is Asn-Pro-Lys-Thr-Asp-Lys-Leu-Val-Asn-Glu-Arg-Leu-Ile-Ser-Met-Ala, beginning at residue 830 and extending toward the C terminus. Membranes containing the 19-kDa fragment have the following functional properties. (i) ATP-dependent functions are absent. (ii) The apparent affinity for occluding Rb is unchanged, the affinity for Na is lower than in the control enzyme, and activation is now strongly sigmoidal rather than hyperbolic. (iii) Membranes containing the 19-kDa fragment can be reconstituted into phospholipid vesicles and sustain slow Rb-Rb exchange. Thus the transport pathway is retained. We conclude that cation occlusion sites and the transport pathway within transmembrane segments are quite separate from the ATP binding site, located on the cytoplasmic domain of the alpha chain. Interactions between cation and ATP sites, the heart of active transport, must be indirect--mediated, presumably, by conformational changes of the protein.